Knowledge on Inquest and Cause of Death– A Study Among Doctors at Teaching Hospital Jaffna - Mayorathan, U.; Pranavan, S.; Moganalakshan, M.; Niroshini, J.S.A.; Jiffry, A.M. (Jaffna Medical Association, 2022)
An inquest is the procedure for investigating sudden deaths in Sri Lanka, a fact-finding exercise rather than a fault-finding inquiry. Giving the correct Cause of Death (COD) is essential from both legal and statistical points of view. Doctors have an important role in both inquest and COD. This study aims to assess the knowledge of inquest and COD among doctors of various hierarchy levels at the teaching hospital, Jaffna. A descriptive cross-sectional study was conducted through systematic random sampling. The questionnaire was distributed and collected in small groups at convenient times with adequate instructions. The total number of participants was 137, among which 44 were consultants, 45 were medical officers, and 48 were intern house officers. Sixty-two subjects had experience more than ten years. Considering the inquest, 37%(N=50) had good, and 61%(N=83) had average knowledge regarding the procedure, 43%(N=58) had good, and 54%(N=73) had average knowledge regarding indications; More than half of the doctors (52%, N=71)) had good, and 29%(N=39) had average knowledge about the doctor’s role in inquest procedure. Regarding COD, 47%(N=64) had good knowledge, while 37%(N=50) had average knowledge. Designation and experience showed a significant association (p-value<0.05) with the overall understanding of inquest, where consultants had good scores. Gender did not significantly correlate with the overall knowledge of inquest and COD. Since a considerable proportion of doctors have average knowledge or below regarding inquest and COD, this is high time to make feasible interventions to upgrade the knowledge among doctors.
Keywords: Inquest; Cause of death; Knowledge; Doctor’s role